2011
DOI: 10.1007/s10637-011-9716-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quinolinyl acrylate derivatives on prostate cancer in vitro and in vivo

Abstract: Quinolines and acrylates are chemical compounds which were previously described as potential antitumor agents. In this study, a series of seven new quinolinyl acrylate derivatives were synthesized and evaluated against human prostate cancer cells PC-3 and LNCaP in vitro and in vivo. The most effective compound (E)-methyl 2-(7-chloroquinolin-4-ylthio)-3-(4 hydroxyphenyl) acrylate reduced the viability in both cell lines in a time- and dose-dependent manner. Inhibitory effects were also observed on the adhesion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 40 publications
2
28
0
1
Order By: Relevance
“…In addition, it has been demonstrated that epigallocatechin gallate (EGCG) induces ROS leading to DNA oxidative damage, which could be responsible for its antitumour actions 6 . QNACR could also inhibits angiogenesis, as we already reported recently in another study 7 and this effect could be due to its pro-oxidative properties besides its actions inhibiting MMP9; indeed neovascularization suppression in vivo and in vitro could be a response of augmenting ROS generation 20 . The involvement of QNACR on angiogenesis inhibition and apoptosis should be addressed in further studies to understand the more specific molecular mechanism of this analogue.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…In addition, it has been demonstrated that epigallocatechin gallate (EGCG) induces ROS leading to DNA oxidative damage, which could be responsible for its antitumour actions 6 . QNACR could also inhibits angiogenesis, as we already reported recently in another study 7 and this effect could be due to its pro-oxidative properties besides its actions inhibiting MMP9; indeed neovascularization suppression in vivo and in vitro could be a response of augmenting ROS generation 20 . The involvement of QNACR on angiogenesis inhibition and apoptosis should be addressed in further studies to understand the more specific molecular mechanism of this analogue.…”
mentioning
confidence: 62%
“…The adaptive response that followed this acute oxidative injury was not sufficient to spare MCF-7 cells from the toxic effects of QNACR. These results suggest that besides its effects on the inhibition of matrix metalloproteases and its ability to decrease tumour growth in animal models 7 , the antitumour activity of this compound could be also involved in the disturbance of the oxidant/antioxidant status. …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations